Problems of Online Learning in the Covid-19 Pandemic Era - Romlah, Romlah; Rosfiani, Okta; Rahayu, Ade Ratna Putri; Syahro, Alfiansyah; Alfian, Nabil (International Journal of Multidisciplinary Approach Research and Science, 2024)
In the era of the COVID-19 pandemic, learning in schools is carried out online to prevent the spread of COVID-19 Schools, teachers, parents, and other parties face many challenges in achieving learning objectives The purpose of this study is to identify the problems of online learning during the Covid-19 pandemic at SMK Muhammadiyah 5 Central Jakarta, DKI Jakarta This research uses a descriptive qualitative approach with a case study method Primary data sources are teachers, deputy heads of infrastructure, parents, and students, and secondary data sources are school principals Participatory observation techniques, in-depth interviews, and documentation were used for data collection. Data were analyzed using the Miles and Huberman interactive model at the stages of data collection, data reduction, data presentation, and conclusion drawing The researcher's investigation revealed several problems: 1) students looking for answers on the Internet, unstable network, decreased motivation to learn. 2) Teachers, namely students rarely submit assignments, off-camera while studying, teachers explain too much theory without explanation, teachers are more interested in teaching online than offline. 3) Deputy Director for Social Infrastructure that there are still students who do not have cell phones or other communication tools to support online learning. There are two students in each class who do not have cell phones. The school provides appropriate equipment, such as Wi-Fi, classrooms, and computers, to enable students who encounter barriers to continue participating in online learning. 4) Parents have limited time to support their children's learning, spend a lot of money on quota and textbooks, and are able to utilize mobile phones as communication tools in online learning.